STUDY OF FACTORS AFFECTING THE INDICATORS OF OIL AND GAS PRODUCTION FROM FIELDS - Abdirazakov, Akmal; Umarkulov, Jabborbek (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article examines the causes of deterioration in the permeability of the bottomhole zone of wells with an increase in the flow rate of oil and gas wells and their main causes: deterioration in the filtration properties of the bottomhole zone during shutdown and repair of wells, division of the bottomhole zone into three, as well as the results of a generalized analysis of hydromechanical, thermochemical, biological factors affecting the permeability of the bottomhole zone of wells, and methods of influencing the bottomhole zone of wells.